A Critical Interpretation On Adharniya Vega According To Classical Samhita - A Brief Review Study - Pandya , Ashwin; Dhakad, Jyoti; Pawar, Shivaji (International Research Journal of Ayurveda & Yoga, 2021)
Adharniya Vegas are the urges which should not be suppressed because they are produced due to unavoidable excreta. The suppression of urges is not a good habit and gives rise to certain problems and disorders. Out of these thirteen, six of them cause Udavartta (reverse movement of Vata). In Sushruta Samhita there is no separate chapter but thirteen types of Vega (Urges) their definition, disorders and treatment are mentioned in chapter Udavartta Pratishedha Acharya Charak has discussed thirteen types of Adharniya Vega (Suppression of Natural urges), their disorders and treatment in Sutra sthana chapter-7. In Ashtanga Hridaya it is quoted that different diseases occur on suppressing the urges and also by producing the urges forcefully. Adharaniya Vega (Suppression of Natural Urges) is one of the foremost causes of all disease. All Ayurvedic texts have mentioned Adharaniya Vega (Suppression of Natural urges) is most important cause for Hridroga (Cardiovascular Disease). Suppression of natural urges is very common in today’s era and especially jobs like office work, taxi driver, teaching etc. and it leads to disease like cardiovascular disease, digestive disorder, gynecological problem, urinary tract infection etc In spite of this suppression of hunger, thirst, sleep, vomiting and Lacrimation are also harmful for the person.